2016
DOI: 10.21037/atm.2016.11.81
|View full text |Cite
|
Sign up to set email alerts
|

Cancer stem cells don’t waste their time cleaning—low proteasome activity, a marker for cancer stem cell function

Abstract: A population of stem-like cells in tumors, the so-called cancer stem cells (CSCs), are being held responsible for therapy resistance and tumor recurrence. In analogy with normal stem cells, CSCs possess the capacity of long term self-renewal and multilineage differentiation. CSCs are believed to be more resistant to various therapies compared to their differentiated offspring and therefore the cause of tumor relapse. Markers for CSCs have been identified using xenograft transplantation assays and lineage traci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…Activity of the 26S proteasome, a protease complex with regulatory functions in cell cycle, DNA repair, and cell survival, is another CSC marker (131, [174][175][176][177]. In this regard, low 26S proteasome activity correlated with high self-renewal capacity and high tumorigenicity in HNSCC cell lines (178).…”
Section: Csc As Biomarkermentioning
confidence: 99%
“…Activity of the 26S proteasome, a protease complex with regulatory functions in cell cycle, DNA repair, and cell survival, is another CSC marker (131, [174][175][176][177]. In this regard, low 26S proteasome activity correlated with high self-renewal capacity and high tumorigenicity in HNSCC cell lines (178).…”
Section: Csc As Biomarkermentioning
confidence: 99%
“…Importantly, Wnt signaling has also been found to be essential for the propagation of cancer stem cells [28]. In conjunction, data show that proteasome complex components were also downregulated in MDA-R cells; low proteasome activity is known to be a potential functional marker for CSC and treatment resistance [29].…”
Section: Resultsmentioning
confidence: 99%
“…28 Tumour cells with low proteasome activity exhibited CSC-like properties and resistance to tumour therapies in various human tumour cells. 50 Spheroid cells were CSC-enriched cells 14,51 exhibiting lower chymotrypsinlike-proteasome activity than adherent cells. 52,53 In this study, time-lapse imaging revealed that the ZsG + cells had self-renewal and differentiation capacity through symmetric and asymmetric divisions.…”
Section: Discussionmentioning
confidence: 99%